The A’jarang Festival – an Innovative Effort for Regional Tourism Development in Jeneponto Regency (Indonesia) - Junaid, Ilham; D’Hauteserre, Anne-Marie (Turizam, 2017)
Innovation in all sectors of development has been the major concern of the Indonesian government including in tourism. Residents, however, are sceptical because Jeneponto regency is a dry area and thus has limited tourism potential. This paper aims at examining whether or not the A’jarang festival is an innovative way to inhance tourism; proposing efforts or strategies to support the festival as tourism innovation; and recommending approaches that can encourage the local government to implement more innovative ways for regional tourism development. The article is based on a qualitative study conducted in 2016. The study reveals that although strategies are needed to support the A’jarang festival, it is considered an innovative effort. The festival should be managed based on the principles of products, processes, markets and managerial innovations. This paper underlines the importance of providing a representative venue and implementing iconic culinary tourism, conferences and seminars, cultural events and creative industries. The local board of tourism needs to strengthen its relationship with eight different community groups including the central and regional government, local leaders, the tourism industry, cultural activists, local community members, academics, non-tourism government institutions and the media.